Influence of amplitude and phase imbalance of quadratures on the noise immunity of coherent reception of signals with quadrature amplitude modulation - G. V. Kulikov; A. A. Lelyukh (Российский технологический журнал)
Quadrature amplitude modulation (QAM) is used for high-speed information transmission in many radio systems and, in particular, in DVB-S and DVB-S2/S2X digital satellite television systems. A receiver included as a part of the transmitting equipment of such systems has a block for the formation of quadrature oscillations used as a reference for signal demodulation. Due to hardware instabilities, amplitude and phase errors may occur, which leads to quadratures imbalance. These inaccuracies cause additional errors in the received signal demodulation. This can significantly degrade the noise immunity of the reception. The paper investigates the influence of amplitude and phase errors in the formation of quadrature oscillations (imbalance of quadratures) on the noise immunity of coherent reception of QAM signals. Using the methods of statistical radio engineering the parameters of the distributions of processes in the receiver are obtained, and the probability of a bit error is estimated. The dependences of the bit error probability on the amplitude unbalance factor, on the phase error of quadrature formation and on signal-to-noise ratio are obtained. It is shown that the amplitude imbalance of the quadratures leads to a significant decrease in the noise immunity of QAM signals reception  at M ≥  16. The acceptable amplitude deviation in this case can be considered to be equal to 5%. At M= 4, the amplitude imbalance in a wide range of values practically does not affect the noise immunity. The phase imbalance of  quadratures  markedly affects the noise immunity of coherent reception of QAM signals. The permissible phase error is no more than 0.05 rad (3 degrees). As the signals positionality increases, this influence also increases.